Lisières et mixtes. (Arras : Noroit - Arras, 1985)
Bonzon, Arièle ; Bruder, Pat ; Carter, Tony ; D'Aiwee, Christian ; Delay, Alexandre ; Delrieu, Bernadette ; Dibbets, Jan ; Gattinoni, Christian ; Gette, Paul Armand ; Gilod, Fabrice ; Kienholz, Edward ; Mechain, François ; Messager, Annette ; Paolini, Guilio ; Sadr, Behdjat ; Sagne, Jean ; Subires, Pascal ; Thomas, Gwenn ; Toma, Kathy ; Trulzsch, Holger ; Vicat-Blanc, Françoise
Lisières et mixtes, Noroit - Arras, Arras, du 23 nov. 1985 au 2 fev. 1986
boek